Age-Dependent Alterations of Cognition, Mitochondrial Function, and Beta-Amyloid Deposition in a Murine Model of Alzheimer’s Disease—A Longitudinal Study - Reutzel, Martina; Grewal, Rekha; Joppe, Aljoscha; Eckert, Gunter P. (Frontiers in Aging Neuroscience, 2022)
Aging is the main risk factor for sporadic Alzheimer's disease (AD), which is mainly characterized by the cerebral deposition of β-amyloid peptides (A and cognitive decline. Mitochondrial dysfunction is also characteristic of the disease and represents a hallmark of both, aging and neurodegeneration. We longitudinally followed A levels, cognition, and mitochondrial function in the same cohort of Thy1-APP751SL mice representing a murine model of AD. In the course of time, changes were most prominent at an age of 13 months including the latency time in the passive avoidance test, the activity of complexes I and IV of the mitochondrial respiration chain, and expression of genes related to mitochondrial biogenesis and synaptic plasticity including Peroxisome proliferator-activated receptor gamma coactivator 1-alpha (PGC1-α), CAMP responsive element binding protein 1 (CREB1), and Synaptophysin 1 (SYP1). These changes occurred in parallel with massively increasing cerebral Aβ levels. Other parameters were changed in younger mice including the alteration rate in the Y-maze test and the nesting score when A levels were not changed yet. The results are consistent in the cohort described. However, previous, non-longitudinal studies reported divergent time points for the occurrence of the parameters studied. These findings are discussed in light of the current results.